2018
DOI: 10.1094/phyto-11-17-0383-r
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization and Expression of PFT, an FHB Resistance Gene at the Fhb1 QTL in Wheat

Abstract: Fusarium head blight (FHB) is a destructive fungal disease in wheat worldwide. Efforts have been carried out to combat this disease, and the pore-forming toxin-like (PFT) gene at the quantitative trait locus (QTL) Fhb1 was isolated and found to confer resistance to FHB in Sumai 3. In this study, we characterized PFT in 348 wheat accessions. Four haplotypes of PFT were identified. The wild haplotype of PFT had higher resistance than other haplotypes and explained 13.8% of phenotypic variation in FHB resistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 41 publications
0
29
0
Order By: Relevance
“…Notably, only the susceptible Syrian landrace ‘Haurani’ possessed the ‘resistant’ PFT haplotype that is in contrast to a study of 40 wheat landraces and cultivars where the PFT allele was exclusively found in FHB resistant lines (Rawat et al 2016 ). In a broader study of 348 hexaploid wheat accessions of mainly Chinese origin, the ‘resistant’ PFT allele existed also in susceptible accessions (He et al 2018 ) and in a collection of 151 cultivars 44 lines were positive for the Wangshuibai/Sumai-3 PFT allele, but only 12 of them were resistant (Jia et al 2018 ). Fhb1 has been introgressed in hexaploid wheat and durum wheat, mostly efficiently improved FHB resistance levels but the recurrent parent had a large impact on the effect of Fhb1 suggesting a large dependency on the genetic background (Von der Ohe et al 2010 ; Salameh et al 2011 ; Balut et al 2013 ; Prat et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, only the susceptible Syrian landrace ‘Haurani’ possessed the ‘resistant’ PFT haplotype that is in contrast to a study of 40 wheat landraces and cultivars where the PFT allele was exclusively found in FHB resistant lines (Rawat et al 2016 ). In a broader study of 348 hexaploid wheat accessions of mainly Chinese origin, the ‘resistant’ PFT allele existed also in susceptible accessions (He et al 2018 ) and in a collection of 151 cultivars 44 lines were positive for the Wangshuibai/Sumai-3 PFT allele, but only 12 of them were resistant (Jia et al 2018 ). Fhb1 has been introgressed in hexaploid wheat and durum wheat, mostly efficiently improved FHB resistance levels but the recurrent parent had a large impact on the effect of Fhb1 suggesting a large dependency on the genetic background (Von der Ohe et al 2010 ; Salameh et al 2011 ; Balut et al 2013 ; Prat et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Optical sorter-based selection operated on detectable differences in seed color only, not seed shape/size or preharvest appearance of the plant. Furthermore, previous research has shown the QTL on 5A contributes mostly to Type I resistance, unlike Fhb1 which contributes to strong Type II resistance (Bai et al, 1999;Buerstmayr et al, 2003;He et al, 2018;Steiner et al, 2019). Therefore, Qfhs.ifa-5A may be more involved in reducing physical kernel damage (shriveled seeds/FDK) and visible preharvest disease symptoms (rating), than differences in seed coat color as a result of FHB infection (FDKos).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of major effect QTL detected for reduced DON accumulation, including Fhb1, co-located with QTL for reduced disease severity on plants preharvest or grains postharvest (Somers et al, 2003;Liu et al, 2012;Liu et al, 2013;Ágnes et al, 2014;Buerstmayr and Lemmens, 2015). Furthermore, Fhb1 has been classified as a strong contributor to Type II FHB resistance, which is associated with reductions in Fusarium damaged kernels (Bai et al, 1999;He et al, 2018). The proportion of Fusarium damaged kernels determined with an optical sorter (FDKos) is a postharvest measure of disease severity on grain as well as an indicator of Type II FHB resistance; therefore, it is not surprising that optical sorter-based among line selection (lines with FDKos values greater than the resistant check were discarded each selection cycle) increased the proportion of lines with Fhb1 (a QTL known to be associated with reduced kernel damage).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rawat et al [105] reported a pore-forming, toxin-like domain conferring FHB resistance for Fhb1. However, markers based on the SNP of this gene do not readily allow the distinction of FHB resistance or susceptible lines when hundreds of lines are assessed [106] . Based on sequencing of the Fhb1 region of near-isogenic lines, fragment deletions and SNP variations of His (histidine-rich calcium binding protein) gene have been identified, and most of the materials lacking 752 bp fragments were scab resistant materials.…”
Section: Molecular Marker-assisted Selectionmentioning
confidence: 99%